Study on Resonance Rayleigh Scattering Spectra, Non-linear Scattering Spectra of Alizarin Red-Cetylpyridinium Bromide-Lead System and its Analytical Application - He, Jia-Hong; Xu, Qiang; Xie, Zhi-Gang; Song, Zhong-Rong (Asian Journal of Chemistry, 2014)
In pH 7.6 NH3·H2O medium, Alizarin red and cetylpyridinium bromide could react with lead to form ternary ion-association complex. As a result, the intensities of resonance Rayleigh scattering and the resonance non-linear scattering such as second-order scattering and frequency-doubling scattering were enhanced greatly. The maximum wavelength of resonance Rayleigh scattering, second-order scattering and frequency-doubling scattering was located at 288, 544 and 390 nm, respectively. The enhancement of the three scattering intensity (DI) was directly proportional to the concentration of lead in the range of 0.12-3.78 μg/mL for resonance Rayleigh scattering, 0.09-2.86 μg/mL for second-order scattering and 0.07-2.86 μg/mL for frequency-doubling scattering] and the detection limits (3s) were 2.1ng/mL for resonance Rayleigh scattering method, 7.4 ng/mL for second-order scattering and 8.6 ng/mL for frequency-doubling scattering], respectively. Therefore, a new, high-sensitive method of resonance Rayleigh scattering and resonance non-linear scattering was developed to determine trace amount of lead. In this work, the characteristic of resonance Rayleigh scattering, second-order scattering and frequency-doubling scattering] spectra of the Alizarin red-cetylpyridinium bromide-Pb(II) system has been studied. Meanwhile, the influence of pH, resonance probe dosage, coexisting substances and other factors were investigated. The results show that the method exhibits a good selectivity, high sensitivity and easy operation. In addition, the mechanism of the enhancement of scattering spectra was discussed.